Communicating with diversities - Tanya le Roux; Annelie Naudé (Communicare)
The South African government set mining companies the target to have women represent 10% of their workforce by 2009. Although the mining companies support the legislation, the target seems almost unreachable and the process riddled with obstacles. This article aims to investigate - within the context within which diversity relating to gender is managed within the South African platinummining industry - the perception of female employees on employer-employee relationships and communication management in a particular mining company. The researchers suggest some interventional steps that can be taken to accommodate female employees in the South African platinum-mining industry.